(untitled) (Third Sector Social Economic Review, 2019)
Most of the agricultural entities operating in Turkey are composed of small family businesses. Recently, government incentives have been increased in order to ensure adequate nutrition of the society and to ensure the continuation of development and agricultural production. Although these supports, there are only three agricultural companies on the stock exchange. The subject of this study is the agriculture entities operating in Borsa Istanbul. These entities must make accounting properly to Turkey Accounting Standards and Turkey Financial Reporting Standards. Accordingly to this, the financial statements and explanations of the agricultural and livestock entities in the stock exchange have been examined. The study shows that, classification of biological assets in companies is common. Biological assets are reported at fair value. Fair value source is explained. Biological assets are classified appropriately in the notes.